The extension of the Bok Bak fault in Northwest Peninsular Malaysia : location and implications - Syed Sheikh Almashoor, (Universiti Kebangsaan Malaysia, 1996)
The Bok Bak fault is a northwest-directed sinistral fault in northwest Peninsular Malaysia whose location was, by late 1980's, quite established. A postulated extension of 450 kilometres to the north-northwest has never been substantiated, but instead, speculated upon. The postulated extension in north Kedah, if there was any, had escaped detection of several mapping exercises, including modern approaches. The weak topography of the area and thick unconsolidated superficial deposits, apparently, are responsible for clouding the sensitivities of the modern methods. However, the conventional approach adopted in this study led to a successful discovery and definition of 82 kilometres of the Bok Bak fault in north Kedah and Perlis up to the Perlis (Malaysia)/Thailand boundary. It is in a dextral six-kilometre offset position with the established counterpart to its south. One significant faultsignature identified is a set of strike ridges which exhibit a left-lateral drag arrangement. Other fault-signatures include, fault planes and breccia, a sharp formational boundary, a spring locality, a lake, two linear rivers, a distorted river's course and a bent watershed line. One fault signature indicates that it is a wrench fault. With a zone of width 800 metres approximately and a total length of 215 kilometres, it is now established that the Bok Bak fault is a major fault in Peninsular Malaysia. Two pairs of correlatable rock units on opposite sides of the fault provide the first ever reliable displacement amount of about 10 km. It is discovered that the limestone hills (mogotes) running from north to central Perlis are not entirely of Chuping Formation. The last hill at the southernmost end (Bukit Ngulang) belongs to Setul Limestone Formation. The formational boundary between these hills, as implied by superficial fault-related features, is a fault contact; and is interpreted as a reliable signature of the Bok Bak fault. Based on similarities in hill-orientation, lithology and fossil contents, the Kodiang limestone mogotes in north Kedah are believed to be the continuation of the Chuping Limestone of central Perlis, but are now dispositioned by the Bok Bak fault.